Skin tight eaudiobook Mick stranahan series, book 1. - Hiaasen, Carl (Mick Stranahan,, 1993)
Bestselling author Carl Hiaasen serves up a humorous helping of "taut, fastpaced action ... crisp and hot" (The New York Times). After dispatching a pistol-packing intruder from his home with the help of a stuffed Marlin head, Mick Stranahan can't deny that someone is out to get him. His now-deceased intruder carries no ID, and as a former Florida state investigator, Stranahan knows there are plenty of potential culprits. His long list of enemies includes an off point hit man, a personal injury lawyer of billboard fame, a notoriously irritating TV journalist, and a fumbling plastic surgeon. Now, if he wants to keep fishing into his golden years, Stranahan has no choice but to come out of retirement to close this one last case ... "Hiaasen display[s] his manic sense of humor at every turn ... wickedly amusing."—Publishers Weekly